AKTIVITAS ANTIOKSIDAN EKTRAK ETANOL 96% DAUN MENGKUDU (MORINDA CITRIFOLIA) DENGAN MENGGUNAKAN METODE DPPH (2,2-DIFENIL-1-PIKRIHIDRAZIL) - Rini, Yanuarti; Hidayati, Nur Afifah; Sadikin, Muhammad (Leuit (Journal of Local Food Security), 2024)
One of the plants that has antioxidants is noni leaves (M. ctrifolia). Thepurpose of this study was to determine the best antioxidant contentbetween old and young noni leaves. The implementation of this study wascarried out in several stages, namely extraction, phytochemicalscreening, total flavonoid test, total phenol test and antioxidant test ofnoni leaf extract using the DPPH (2,2-diphenyl-1-picylhydrazyl) method.The results obtained for the IC50 value of the ethanol extract of old nonileaves were 309.99 ± 0.90 µg / ml, young noni leaf extract 255.33 ± 0.12µg / ml, and quercetin 4.09 ± 0.10 µg / ml. The antioxidant activity ofnoni leaves with better results is young noni leaves. The total phenol testresults of old noni leaves were 584.79 mg/kg and the results of youngnoni leaves were 543.42 mg/kg. The total flavonoid test results of old nonileaves were 5.20±0.16 mg QE/g and the results of young noni leaves were7.08±0.14 mg QE/g.